The making of a masterpiece and the power of poetry: “An October Salmon” by Ted Hughes - McCall, Michael John (Curtin University, 2015)
The Making of a Masterpiece and the Power of Poetry: “An October Salmon” by Ted Hughes is a philosophical reflection based on my lived experiences and engagement with the poetry of Ted Hughes, with particular reference to his poem “An October Salmon”. It is directed phenomenologically and autoethnographically towards the idea of using the power of poetry in an educational context to promote and facilitate the teaching of “respect” for self, others and the world.